Innovative Strategies for State Civil Apparatus (ASN) Performance Management in Improving Bureaucratic Professionalism in the Regional Personnel Agency of Sidoarjo Regency - Fedianty Augustinah; Ficha Indriana; Eny Haryati (International Journal of Social Science and Humanity, 2025)
This research intends to examine novel performance management techniques for Civil Servants (ASN) to improve bureaucratic professionalism at the Regional Civil Service Agency (BKD) in Sidoarjo Regency. The research arises from the increasing use of digital performance systems via the e-Performance application, which has yet to show notable changes in behavior among bureaucrats. The study examines the efficiency of the e-Performance system, organizational culture, leadership roles, and management innovations at BKD. Employing a qualitative case study method, data were gathered through extensive interviews, observations, and document review with structural officials and staff. The results indicate that the e-Performance system has enhanced administrative efficiency and transparency, yet it still falls short in fostering employee participation and feedback processes. Deficiencies in digital skills and insufficient training for fostering culture were noted as well. The research suggests fostering a reflective workplace culture centered on recognition, ongoing digital skills training, and establishing a reciprocal feedback mechanism in performance assessments. Working with outside organizations is crucial to maintain accountability and impartiality. These results are anticipated to enhance ASN professionalism and foster an adaptive, innovative bureaucracy in the era of digital governance.